ISLAMIC EDUCATION VALUES IN THE TALLASA KAMASE-MASE TRADITION TO STRENGTHEN THE RELIGIOUS MODERATION OF THE INDIGENOUS PEOPLE OF AMMATOA KAJANG - Windi Pratiwi Yusdar; A. Marjuni; Munawir Kamaluddin (LP2M IAIN Sultan Amai Gorontalo, 2026)
The Tallasa Kamase-Mase tradition was regarded as a cultural heritage of the Ammatoa indigenous community in Kajang, Bulukumba Regency, which instilled values of simplicity, balance, and harmony in everyday life. Amidst the increasing complexity of contemporary religious life, exploring how local wisdom could strengthen religious moderation was essential. This study was conducted to analyze the Islamic educational values internalized within the Tallasa Kamase-Mase tradition and its contribution to shaping the moderate attitudes of the Ammatoa community. A qualitative approach was employed using ethnographic methods, including participatory observation, in-depth interviews, and documentation. Triangulation of sources, techniques, and time was applied to ensure the validity of the data. Twelve Islamic educational values were identified within the Tallasa Kamase-Mase tradition, covering the dimensions of creed, worship, ethics, social interaction, and scientific-ecological understanding. These values aligned with ten principles of religious moderation, such as tawassuth, tasamuh, musawah, and muḥākamah. The findings indicated that local wisdom was compatible with Islamic values and effective in shaping inclusive religious character. The study was concluded to offer both theoretical and practical contributions to the development of Islamic education rooted in local cultural wisdom.